MODELING OF OXYGEN MODE INDICATORS IN THE CONDITIONS OF THE AQUATIC ECOSYSTEM OF THE DNEPR BASIN - Ponomarenko, R.; Plyatsuk, L.; Tretyakov, O.; Ablieieva, I. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2020)
The article investigates the adequacy of the mathematical model of oxygen regime prediction in the aquatic ecosystem of the Dnieper basin on the basis of the classical model of Streiter-Phelps, as well as its modification. A retrospective analysis of the oxygen parameters of the Dnieper River was carried out, which revealed trends in the deterioration of the river's oxygen regime and an increase in the rate of biological oxygen consumption by annual average. The mathematical model of the dynamics of the integral indicators of the ecological status of the reservoir has been improved by supplementing the correction coefficients, which allows to predict with sufficient accuracy the change in the ecological status of the Dnieper.